Predicting higher education outcomes and implications for a postsecondary institution ratings system. Issue 4 (3rd July 2016) - Walker II, Eddie G.
ABSTRACT: The accountability of colleges and universities is a high priority for those making policy decisions. The purpose of this study was to determine institutional characteristics predicting retention rates, graduation rates and transfer-out rates using publicly available data from the US Department of Education. Using regression analysis, it was determined there are 14 predictors of the full-time retention rate, 7 predictors of the part-time retention rate, 15 predictors of the graduation rate and 12 predictors of transfer-out rates. Institutions and policymakers could use the results of this analysis to determine the policies that would be beneficial to improving the analysed outcomes. All four analyses indicate good fit with R 2 ranging from .273 to .828. Some possible policy implications include addressing selectivity if institutions want to improve retention rates and addressing affordability to improve retention and graduation rates.